2017
DOI: 10.1071/he16095
|View full text |Cite
|
Sign up to set email alerts
|

Achieving equity in Crunch&Sip®: a pilot intervention of supplementary free fruit and vegetables in NSW classrooms

Abstract: Issue addressed Anecdotal evidence from teachers in Western Sydney Local Health District (WSLHD) indicated that many primary school children are regularly unable to participate in the Crunch&Sip (C&S) program (breaks during class time to eat fruit and/or vegetables and drink water) as they do not bring produce from home. Actual reach of the program may therefore be currently overestimated, and inequitable. This study examined the feasibility, acceptability and efficacy of providing school children supplementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…This is consistent with other studies that suggest additional and/or different dissemination strategies are required to facilitate a greater adoption of policies and practice within schools. [9,33] While we found there were positive changes in many weight-related behaviours which were generally in the same direction and of the same magnitude for Aboriginal and non-Aboriginal children, adiposity prevalences were higher in 2015 than 2010 for all children and were consistently higher among Aboriginal children. This may indicate there are issues with the fidelity and quality of the delivery of these programs in some schools.…”
Section: Addressing the Health Inequality Gap Between Aboriginal And supporting
confidence: 49%
“…This is consistent with other studies that suggest additional and/or different dissemination strategies are required to facilitate a greater adoption of policies and practice within schools. [9,33] While we found there were positive changes in many weight-related behaviours which were generally in the same direction and of the same magnitude for Aboriginal and non-Aboriginal children, adiposity prevalences were higher in 2015 than 2010 for all children and were consistently higher among Aboriginal children. This may indicate there are issues with the fidelity and quality of the delivery of these programs in some schools.…”
Section: Addressing the Health Inequality Gap Between Aboriginal And supporting
confidence: 49%
“…Similar findings have been shown elsewhere and data from the NSW Schools Physical Activity and Nutrition Survey (2015) and national data confirm that children are much more likely to meet guidelines for fruit intake than vegetable intake . This suggests that a focus on vegetables as a separate entity rather than as a combined entity with “fruits and vegetables” is needed to increase children's vegetable intake to meet Australian dietary guidelines for vegetables …”
Section: Discussionmentioning
confidence: 99%
“…4 This suggests that a focus on vegetables as a separate entity rather than as a combined entity with "fruits and vegetables" is needed to increase children's vegetable intake to meet Australian dietary guidelines for vegetables. 17,18 Systematic reviews examining school-based programs to improve fruit and vegetable intake and dietary intake in general have shown that multi-component interventions are most effective but that intensity of the intervention did not result in further improved intake in the longer term. 7,19,20 This is reinforced in our evaluation in which the positive effects of this low-intensity intervention were largely sustained for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…8 Subsidisation may be one way to ameliorate this barrier whereby the provision of free fruit and vegetables in disadvantaged schools was recently found to be an effective way to significantly increase their consumption. 9 However, sourcing sustainable funding for community-based subsidy programmes is likely to be challenging. 9 Evidence ultimately suggests that behavioural change interventions will continue to be met with limited success in the absence of policies which act upon these structural barriers to healthy eating, particularly in disadvantaged groups.…”
Section: Major Themes Subthemesmentioning
confidence: 99%
“…9 However, sourcing sustainable funding for community-based subsidy programmes is likely to be challenging. 9 Evidence ultimately suggests that behavioural change interventions will continue to be met with limited success in the absence of policies which act upon these structural barriers to healthy eating, particularly in disadvantaged groups. 10 Policies which support access to affordable, healthy foods should be the focus of future research.…”
Section: Major Themes Subthemesmentioning
confidence: 99%